Molecular beacon anchored onto a graphene oxide substrate. (21st August 2017) - Darbandi, Arash; Datta, Debopam; Patel, Krunal; Lin, Gary; Stroscio, Michael A; Dutta, Mitra
Abstract: In this article, we report a graphene oxide-based nanosensor incorporating semiconductor quantum dots linked to DNA-aptamers that functions as a 'turn-off' fluorescent nanosensor for detection of low concentrations of analytes. A specific demonstration of this turn-off aptasensor is presented for the case of the detection of mercury (II) ions. In this system, ensembles of aptamer-based quantum-dot sensors are anchored onto graphene oxide (GO) flakes which provide a platform for analyte detection in the vicinity of GO. Herein, the operation of this ensemble-based nanosensor is demonstrated for mercury ions, which upon addition of mercury, quenching of the emission intensity from the quantum dots is observed due to resonance energy transfer between quantum dots and the gold nanoparticle connected via a mercury target aptamer. A key result is that the usually dominant effect of quenching of the quantum dot due to close proximity to the GO can be reduced to negligible levels by using a linker molecule in conjunctions with the aptamer-based nanosensor. The effect of ionic concentration of the background matrix on the emission intensity was also investigated. The sensor system is found to be highly selective towards mercury and exhibits a linear behavior ( r 2 > 0.99) in the nanomolar concentration range. The detection limit of the sensor towards mercury with no GO present was found to be 16.5 nM. With GO attached to molecular beacon via 14 base, 35 base, and 51 base long linker DNA, the detection limit was found to be 38.4 nM, 9.45 nM, and 11.38 nM; respectively.